COST AND OUTPUT RELATIONSHIPS. - Avery, Harold G.; Pollack, M. (The Accounting Review, 1946)
Abstract A study of recent accounting literature discloses a very limited use of ratios and percentages to determine the effect of changes in costs and output on the final unit cost. Most of the literature, especially in the case of budget forecasting, approaches the problem by showing the changes in costs and output in terms of absolute amounts. For this article the problem and solution method is believed to be the most succinct manner for presenting this material. The first problem will show the effect on unit cost of various changes in total cost and unit output, the second will deal specifically with the determination of unit meal cost when changes are contemplated in total meal costs and number of meals served, and the third will show the unit output necessary to cover increased costs of production if unit cost is to remain the same. In all these problems, unit costs will vary in inverse proportion to output. Cost and output relationships can be measured by percentages and ratios. The article presents a formulae, which can be used as an expedient device to determine the effect of variations in cost and output relationships.